Low sexual function is associated with menopausal status in mid-aged women with human immunodeficiency virus infection - Mezones-Holguín, Edward (2022)
OBJECTIVE: To assess the association between menopausal status and female sexual function among mid-aged women with human immunodeficiency virus (HIV) infection. METHODS: We carried out a cross-sectional study of 221 sexually active HIV-infected women ages 40 to 59 years, based on a secondary analysis of a three-hospital survey in Lima, Perú. We classified menopausal status according to Stages of Reproductive Aging Workshop criteria (STRAW+10); this exposure variable was categorized as binary (non-postmenopausal and postmenopausal) and-for exploratory analysis-as multinomial (pre-, peri-, and postmenopausal). We defined low sexual function (LSF) using the 6-item Female Sexual Function Index (total score ≤19). Socio-demographic and clinical variables were assessed, including age, used highly active antiretroviral therapy scheme, disease duration, depressive symptoms, and co-morbidities. We performed Poisson generalized linear models with a robust variance to estimate 95% confidence interval (CI), crude prevalence ratios (cPRs), and adjusted prevalence ratios (aPRs) by epidemiological and statistical approaches using nonparametric method of bias-corrected and accelerated bootstrap resampling with 1,000 repetitions. RESULTS: Studied women had a median age of 47.0 years (interquartile range: 7.5); 25.3% were premenopausal, 25.8% were perimenopausal, and 48.9% were postmenopausal. Also, 64.3% had LSF. The frequency of LSF was 53.6% in non-postmenopausal and 75.0% in postmenopausal women. Postmenopausal status was associated with LSF in both the crude (cPR = 1.39; 95% CI: 1.13-1.71) and the adjusted regression models (aPR = 1.38; 95% CI: 1.12-1.71). CONCLUSIONS: HIV-infected postmenopausal women have a higher prevalence of LSF than those non-postmenopausal ones, even when adjusting for multiple potential confounders.